(untitled) (Journal of Global Arts Studies, 2025)
Background： With the rapid advancement of information technology, aesthetic education in higher education is undergoing a profound digital transformation. This transformation not only reshapes instructional methodologies but also exerts a significant influence on pedagogical paradigms and students’ aesthetic development. Objective： This study aims to explore the necessity of digital transformation in aesthetic education within higher education, examine the existing challenges, and propose viable pathways for overcoming these difficulties to foster high-quality development in aesthetic education. Methods： This study investigates the digital transformation of aesthetic education in higher education through literature review and case study analysis. It explores the challenges of integrating digital technologies into teaching and examines the interplay between technological tools and educational goals. Results： The paper proposes five strategic measures: building a systematic instructional framework, integrating AI to enhance teaching, encouraging interdisciplinary collaboration, innovating teaching methods, and fostering digital citizenship. These aim to improve the quality and relevance of aesthetic education in the digital era. Conclusion： The study highlights the significant impact of digital technologies on pedagogical models and educational philosophy. It contributes to both theoretical and practical discussions on the sustainable development of aesthetic education and offers insights for future innovation.